Schnitzler syndrome refractory to anakinra: successful treatment with canakinumab - Angel Luis Salcedo-Mingoarranz; María Dorado-Fernández; Sofía García-Martínez; Paz Collado-Ramos; Nicolás Silvestre-Torner (Taylor & Francis Group, 2023)
Schnitzler syndrome (SchS) is a rare autoimmune and inflammatory disease mediated by interleukin-1 beta (IL-1β). Recurrent monoclonal gammopathy and chronic urticarial rash are the symptoms required for diagnosis according to the Strasbourg criteria. The low prevalence of this syndrome (around 300 cases have been reported) and confusion with other inflammatory disorders may delay the diagnosis for up to 5 years. Although the most effective treatment for SchS is anakinra, some patients do not respond to this treatment. We report a case of SchS in a 64-year-old woman with multiple episodes of fever, severe rash, erythema, arthralgia and dyspnea. The patient was successfully treated with canakinumab after anakinra intolerance and failure of colchicine, prednisone, methotrexate and dapsone. After the first dose of canakinumab the skin wounds rapidly improved and the patient did not require any concomitant treatments. The cause of SchS is still unknown and a differential diagnosis is recommended, especially with adult-onset Still´s disease due to their similar symptoms. Canakinumab, a specific anti-IL-1β antibody, blocks its binding to receptors, thereby preventing IL-1β-induced gene activation and production of inflammatory mediators. Canakinumab has proven to be an effective drug in SchS, providing an alternative to anakinra.